Caregiver Protective Behavior, Toddler Fear and Sadness, and Toddler Cortisol Reactivity in Novel Contexts. (8th September 2012) - Hutt, Rachel L.; Buss, Kristin A.; Kiel, Elizabeth J.
<x xml:space="preserve">Abstract</x> Previous research has shown that caregiver protective behavior may exacerbate toddler distress in specific contexts. This study sought to extend this work to examine associations between these variables and toddler cortisol reactivity. Ninety‐three 24‐month‐old toddlers were observed across six novel contexts designed to elicit distress. Toddlers were asked to give saliva samples at the beginning and end of the laboratory procedure. Toddler sadness, toddler fear and caregiver protective behavior were coded. Results indicate that caregiver protective behavior accounted for the association between toddler sadness and cortisol reactivity where higher levels of protective behavior were associated with higher cortisol reactivity. This study showed that caregiver protective behavior, which functions to prevent a child from interacting with a novel stimulus, is an important mechanism to consider when understanding toddler stress responses during novel contexts.